Green synthesis of selenium nanoparticles conjugated Clausena dentata plant leaf extract and their insecticidal potential against mosquito vectors. (17th November 2017) - Sowndarya, P.; Ramkumar, G.; Shivakumar, M. S.
Abstract: Mosquitoes are major vectors for the transmission of many diseases like chikungunya, malaria, dengue, zika, etc. worldwide. In the present study, selenium nanoparticles (SeNPs) were synthesized from Clausena dentata and were tested for their larvicidal efficacy against the fourth-instar larvae of Anopheles stephensi, Aedes Aegypti, and Culex quinquefasciatus . The synthesized nanoparticles were characterized using UV-Vis spectroscopy, Fourier Transform Infrared Radiation (FTIR) spectroscopy, EDaX, and SEM. The results recorded from UV-Vis spectroscopy show the peak absorption spectrum at 420 nm. In FTIR, the maximum peak value is 2922.25 cm −1 assigned to N-H group (amide group). In EDaX analysis shows peak around 72.64 which confirm the binding intensity of selenium. In SEM analysis, the synthesized SeNPs sizes were ranging from 46.32 nm to 78.88 nm. The synthesized SeNPs produced high mortality with very low concentration (LC50 ) were 240.714 mg/L; 104.13 mg/L, and 99.602 mg/L for A. stephensi, A. Aegypti, and C. quinquefasciatus, respectively. These results suggest that the C. dentata leaf extract-mediated biosynthesis of SeNPs has the potential to be used as an ideal ecofriendly approach toward the control of mosquito vectors at early stages.